Studi Tentang Pembelajaran Multidisiplin dan Hubungannya dengan Kemampuan Berpikir Kompleks - Wagiman Manik; Ahmad Sulaiman Siregar; Saiful Islam Abizar; Yudi Rahayu; Muhammad Iqbal; Sulthani Mukhlis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The 21st century is marked by the advancement of science and technology, driving increasingly complex changes in life. In the context of education, a multidisciplinary learning approach has become relevant in enhancing students' complex thinking abilities. This approach allows students to integrate various disciplines in solving existing problems, thereby improving their critical, analytical, and creative thinking skills. This study explores the relationship between multidisciplinary learning and students' complex thinking abilities, the factors influencing its implementation effectiveness, and effective multidisciplinary learning strategies. Based on previous research, multidisciplinary learning has been proven to enhance complex thinking skills by up to 35% compared to conventional learning methods. However, its implementation faces several challenges, including a lack of teacher readiness, limited resources, and a learning culture that still emphasizes rote memorization. Therefore, problem-based learning strategies, cross-disciplinary collaboration, and the use of technology are recommended to improve the effectiveness of this approach.